A Tracer Study on the Perceived Impact of Leadership of the University of the Philippines School of Library and Information Studies (UP SLIS) Bachelor of Library and Information Science (BLIS) Student Council (SC) to Post-graduation Professional Life - Apolinario, Rhea Rowena; Oasan, Jan Paul (Qualitative and Quantitative Methods in Libraries; Vol 10 No 3 (2021): September issue 2021, 2021)
This study is a descriptive research which sought to find out what has become of former UP School of Library and Information Studies student council members post-graduation and their perception of the impact of having undertaken leadership roles on the college-level on their development as professionals, in terms of student leadership competencies, and of characteristics and competencies of a modern LIS professional. The study utilized survey questionnaire with population and sample being former student council member graduates of the UP SLIS for the period 2003-2018. Data collected were analyzed using statistics and graphs. The study found that the graduates are generally employed, practicing in the LIS field, if not taking up post-graduate studies. Most respondents, a year after graduation, have received increased remunerations. Their general perception of experiences with the UP SLIS SC is positive. Specifically, they perceive student leadership competencies and non-traditional competencies of LIS professionals as being well improved upon, though they feel the opposite with regards to traditional LIS competencies.  Though not necessarily determinant of their outcomes, these now professionals' experiences with the UP SLIS SC have guided them to their respective states.